V. Tairov (1859-1938) scientific and organizational activity as a member of Viticultural Committee and in the frame of viticulturists and wine-makers congresses - Burlak, G. V. (History of science and technology, 2018)
Scientific and organizational activity of Professor V. Tairov at the end of ХІХ – beginning of ХХ centuries has been highlighted. Out-of-the-way items of pages on V. Tairov’s life and activity as a member of the Viticulture Committee have been considered. The practical activities of the scientist, his cooperation with the Odesa Viticulture Committee, participation in the congresses organized by the Committee, and in the international congresses have been characterized. The significance of the scientist’s ideas for the viticulture has been demonstrated.